2017
DOI: 10.1111/aab.12329
|View full text |Cite
|
Sign up to set email alerts
|

The ever increasing diversity of begomoviruses infecting non‐cultivated hosts: new species from Sida spp. and Leonurus sibiricus, plus two New World alphasatellites

Abstract: Begomoviruses (whitefly-transmitted, single-stranded DNA plant viruses) are among the most damaging pathogens causing epidemics in economically important crops worldwide. Besides cultivated plants, many weed and wild hosts act as virus reservoirs where recombination may occur, resulting in new species. The aim of this study was to further characterise the diversity of begomoviruses infecting two major weed genera, Sida and Leonurus. Total DNA was extracted from samples collected in the states of Rio Grande do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 82 publications
0
24
0
1
Order By: Relevance
“…We used these RCA-RFLP comparisons to assess the potential problem of generating chimeric begomovirus genomes that could derive from the assembly of sequences belonging to different species in a mixed infection sample. There are several reports about the occurrence of mixed infection in the field, caused by the transmission of the viruses by the same vector [12,55,63,71]. However, in this work, we only detected single infections in pepper.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We used these RCA-RFLP comparisons to assess the potential problem of generating chimeric begomovirus genomes that could derive from the assembly of sequences belonging to different species in a mixed infection sample. There are several reports about the occurrence of mixed infection in the field, caused by the transmission of the viruses by the same vector [12,55,63,71]. However, in this work, we only detected single infections in pepper.…”
Section: Discussionmentioning
confidence: 57%
“…This was the first record of an alphasatellite infecting pepper and the first alphasatellite reported in Argentina. ToYSA 2 is phylogenetically related to alphasatellites associated with new world begomoviruses in non-cultivated plants, like euphorbia yellow mosaic alphasatellite (EuYMA) identified in Euphorbia heterophylla and Sida spp., cleome leaf crumple alphasatellite (ClLCrA) in Cleome affinis, and tomato yellow spot alphasatellite (ToYSA) in Leonurus sibiricus (synonym L. japonicus) [68,71,72]. We found ToYSA 2 associated with ToYSV in L. japonicus and pepper, showing that it could be transferred from weed to crop or vice versa.…”
Section: Discussionmentioning
confidence: 88%
“…In the New World where monopartite begomoviruses are very rare, betasatellites have not been identified and alphasatellites have only ever been reported to occur in association with bipartite Begomovirus infections [10,32,37].…”
Section: Introductionmentioning
confidence: 99%
“…Ferro et al . () used rolling circle amplification, a powerful technique for detection and amplification of circular DNA molecules, to characterise begomoviruses infecting wild hosts from two plant genera, Sida and Leonorus , in Brazil. After sequencing 78 DNA clones, the authors identified isolates not only from four known begomoviral species, but also belonging to three new begomoviral species, as well as a new alphasatellite (Ferro et al ., ).…”
mentioning
confidence: 99%
“…() used rolling circle amplification, a powerful technique for detection and amplification of circular DNA molecules, to characterise begomoviruses infecting wild hosts from two plant genera, Sida and Leonorus , in Brazil. After sequencing 78 DNA clones, the authors identified isolates not only from four known begomoviral species, but also belonging to three new begomoviral species, as well as a new alphasatellite (Ferro et al ., ). Cataloguing the viral diversity in wild species is highly significant and interesting, as wild species may constitute a diversity reservoir for viruses which may jump from wild to cultivated hosts resulting in emerging diseases in crops (Woolhouse et al ., ), and these may have potentially devastating consequences.…”
mentioning
confidence: 99%